MASUKNYA ISLAM DI PALEMBANG PADA ABAD 7 MASEHI SEBAGAI SUMBER BELAJAR SEJARAH DIGITAL DI SMA PGRI 2 PALEMBANG - Notaris, M; Nindiati, Dina Sri; Zamhari, Ahmad (Universitas Batanghari Jambi, 2025)
The purpose of this study is to investigate the history of Islam's entry into Palembang and to determine the relevance of this event as a source for learning digital history. The method used is literature review or library research. The data collection techniques used consist of interviews and document studies. The results of this study obtained that the Srivijaya Kingdom located in the city of Palembang, the entry of Islam in Palembang through traders from the Middle East came at the same time as bringing the religion they embraced (Islam) in the 7th-8th century AD, with the flexible nature of traders and the friendly nature of the native population has caused the growth of this new understanding to run peacefully. The Srivijaya Kingdom established relations with rulers in the Middle East during the Umayyad dynasty, under the reign of Abdul Aziz in 717 AD, establishing economic cooperation. The implementation of the results of the study that the material on the entry of Islam in Palembang is still very relevant to be taught to students because of the values contained, in the form of digital learning resources is expected to increase students' interest in learning the history of the entry of Islam in Palembang.